2005
DOI: 10.1037/0893-164x.19.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Measuring adolescent smoking expectancies by incorporating judgments about the expected time of occurrence of smoking outcomes.

Abstract: French and English Canadian adolescents completed a smoking expectancy questionnaire and 2 measures of current smoking status. Multiple regression revealed that beliefs about the expected time of occurrence of smoking outcomes explained unique variance in current smoking after controlling for judgments about the probability and desirability of these outcomes. In addition, the relationship between the perceived probability of the general costs of smoking and current smoking was moderated by beliefs about the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(61 reference statements)
2
6
0
Order By: Relevance
“…A large body of literature supports the important relationship that expectancies play in adolescent smoking behavior. For example, studies have shown adolescents' smoking-related expectancies are related to both their smoking intention (Bauman & Chenoweth, 1984;Robinson & Klesges, 1997) and to their smoking behavior (Hine, Tilleczek, Lewko, McKenzie-Richer, & Perreault, 2005;Mayhew et al, 2000). Similar findings have been observed in studies of Latino youth, with positive outcome expectancies (Spruijt-Metz, Gallaher, Unger, & Anderson-Johnson, 2004Unger at al., 2000), negative outcome expectancies (Unger et al, 2000), and attitudinal beliefs (Elder et al, 2000) being related to smoking behaviors and intentions.…”
Section: An Integrated Conceptual Frameworksupporting
confidence: 66%
“…A large body of literature supports the important relationship that expectancies play in adolescent smoking behavior. For example, studies have shown adolescents' smoking-related expectancies are related to both their smoking intention (Bauman & Chenoweth, 1984;Robinson & Klesges, 1997) and to their smoking behavior (Hine, Tilleczek, Lewko, McKenzie-Richer, & Perreault, 2005;Mayhew et al, 2000). Similar findings have been observed in studies of Latino youth, with positive outcome expectancies (Spruijt-Metz, Gallaher, Unger, & Anderson-Johnson, 2004Unger at al., 2000), negative outcome expectancies (Unger et al, 2000), and attitudinal beliefs (Elder et al, 2000) being related to smoking behaviors and intentions.…”
Section: An Integrated Conceptual Frameworksupporting
confidence: 66%
“…Relatedly, without temporal data, we cannot establish that smoking expectancies in ADHD adolescents will necessarily lead to smoking initiation. However, smoking expectancies are considered a robust predictor of eventual smoking behavior [11,13]. Future research should use a longitudinal design to examine dynamic trajectories of ADHD symptoms, smoking precursors (i.e., expectancies), and early smoking behavior milestones (i.e., puff, inhalation, whole cigarette [35]).…”
Section: Discussionmentioning
confidence: 99%
“…These intervening cognitions refer to one's anticipation of a systematic relationship between the event and expected outcome [10]. According to the widely accepted Expectancy Mediation Hypothesis, expectancies may be a proximal cause of behavior and may mediate distal effects [11]. Some experimental evidence supports a causal role, as laboratory manipulation of expectancies has led to behavior change [12].…”
mentioning
confidence: 99%
“…Expected consequences of smoking cigarettes were assessed using 43 items (see the Appendix). Most of the items were taken directly from a 50-item smoking expectancy measure previously used by Hine et al (2002Hine et al ( , 2005. This original scale was developed from semistructured and open-ended interviews with 20 smokers and 20 nonsmokers, ages 12 to 18.…”
Section: Methodsmentioning
confidence: 99%